Evidence for expiratory flow limitation of extrathoracic origin in patients with obstructive sleep apnoea. Issue 5 (1st May 2002) - Verin, E; Tardif, C; Portier, F; Similowski, T; Pasquis, P; Muir, J F
Abstract : Background: A study was undertaken to examine the expiratory flow response to a negative pressure (NEP) applied at the airway in patients with no abnormalities of the intrathoracic airway but suffering from the obstructive sleep apnoea syndrome (OSAS). Methods: Nineteen patients with OSAS with normal spirometric values were studied. NEP of –5 cm H2 O and –10 cm H2 O was applied to the mouth when sitting and when supine. Results: Thirteen patients exhibited expiratory flow limitation when supine (group 1). Of these, three also had flow limitation in the sitting position. The remaining six patients (group 2) had no flow limitation. Patients in groups 1 and 2 were similar with respect to age, sex, and body mass index, but the apnoea/hypopnoea index (AHI) was higher in group 1 than in group 2 (p<0.05). There was a significant correlation between the degree of flow limitation (expressed as a percentage of the expired tidal volume over which the NEP induced flow did not exceed spontaneous flow) and the AHI (p<0.05 for both pressure levels) as well as the desaturation index (DI, number of desaturations per hour of sleep; p<0.05 at –10 cm H2 O). Conclusion: This study confirms that the NEP technique can detect expiratory flow limitation of extrathoracic as well as of intrathoracic origin. This technique could be useful for studying the collapsibility of the passive upper airway in awake subjects and might help to predict the severity of OSAS.